Pengaruh Manajemen Pengetahuan dan Perilaku Kerja Inovatif terhadap Kinerja Organisasi melalui Kompetensi Guru sebagai Variabel Mediasi di Bidang Pendidikan - Pricill, Yuddy Giovanna; Cesy, Angelica Cleryn; Mon, Muhammad Donal (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of knowledge management (KM) and innovative work behavior (IWB) on the performance of educational organizations through teacher competence as a mediating variable. The research seeks to examine how KM and IWB contribute to enhancing teacher competence and, consequently, organizational performance in the education sector. The population of this study consists of private senior high school teachers in Batam City, with a sample of 185 respondents selected using purposive sampling. The research instrument was a five-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using Partial Least Squares (PLS) through the evaluation of the measurement model (outer model) and structural model (inner model). The results indicate that KM and IWB have a positive and significant effect on teacher competence, with path coefficient values of 0.521 and 0.332, respectively. Teacher competence plays a significant role as a mediator in improving organizational performance, with indirect effect contributions of 0.430 for KM and 0.274 for IWB. This study highlights the integration of knowledge management and innovative work behavior in the educational context, particularly in enhancing teacher competence. The novelty of this research lies in using teacher competence as a mediating variable linking KM and IWB to organizational performance, an approach that is still rarely examined empirically in formal education in Indonesia.The findings provide practical implications for educational policymakers, particularly school management, to design programs that enhance teacher capacity based on knowledge and innovation sustainably. Developing teacher competence strategically can directly improve the effectiveness and competitiveness of educational organizations..